Vórtices Ciclônicos de Médios Níveis (VCMN): uma análise de frequência e estrutura - Santos, Deydila Michele Bonfim dos (2012)
Middle Tropospheric Cyclonic Vortexes (MTCV) were observed only in middle atmosphere (between 700 and 400 hPa) in tropical region of the Southern Atlantic. Analysis of frequencies, localization and duration of the MTCVs during three years (2008, 2009 and 2010) were the principal study goal. The MTCV were identified and analyzed using NCEP (National Centers for Environmental Prediction) reanalysis data (stream lines), on 9 patterns levels; a total of 39420 image maps. The 696 MTCV were observed during three years; minimal number was 204 in 2010 and maximal 248 in 2008. They were located mainly over the ocean in the range between 6° S -18° S. Lower frequencies of MTCV are observed in spring and winter (21.3% and 25.9% respectively) and the season with more frequency was the summer (26.6%); it is noted little seasonal variability. The MTCV duration was short, between 6 and 12hours in 70,7% of events. In the case studies, were observed a potential vorticity center of -0.5 and -1.0 PVU in the region of MTCV, weak cyclonic vorticity. The MTCV was associated with large scale systems, such as ITCZ, SACZ and CJS.